2017
DOI: 10.1016/j.jad.2017.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Perceived emotional social support in bereaved spouses mediates the relationship between anxiety and depression

Abstract: Background Prior research has shown that anxiety symptoms predict later depression symptoms following bereavement. Nevertheless, no research has investigated mechanisms of the temporal relationship between anxiety and later depressive symptoms or examined the impact of depressive symptoms on later anxiety symptoms following bereavement. Methods The current study examined perceived emotional social support as a possible mediator between anxiety and depressive symptoms in a bereaved sample of older adults (N =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 105 publications
2
52
0
5
Order By: Relevance
“…Relational factors such as mechanisms of these asssociations have been found taking GAD or anxiety symptoms as predictive of depression. For example, low perceived emotional social support have been found to be mediator in the association between depressive and anxiety symptoms 48 months later for bereaved individuals (Jacobson, et al, 2017b), interpersonal oversensitivity and social chronic stress have been found as mediating the relationship between GAD before age 15 and later depression (Starr et al, 2014), and perceptions of not being accepted or loved were found to significantly mediate the relationship between adolescent anxiety and clinical depression in adulthood (Jacobson & Newman, 2016). However, no prior research has examined the mechanism of this relationship in an older adult population.…”
Section: Introductionmentioning
confidence: 99%
“…Relational factors such as mechanisms of these asssociations have been found taking GAD or anxiety symptoms as predictive of depression. For example, low perceived emotional social support have been found to be mediator in the association between depressive and anxiety symptoms 48 months later for bereaved individuals (Jacobson, et al, 2017b), interpersonal oversensitivity and social chronic stress have been found as mediating the relationship between GAD before age 15 and later depression (Starr et al, 2014), and perceptions of not being accepted or loved were found to significantly mediate the relationship between adolescent anxiety and clinical depression in adulthood (Jacobson & Newman, 2016). However, no prior research has examined the mechanism of this relationship in an older adult population.…”
Section: Introductionmentioning
confidence: 99%
“…Dukungan sosial emosional dapat memediasi antara gejala kecemasan dan gejala depresi pada lansia yang telah kehilangan pasangan (Davies, Crowe, & Whitehead, 2016;Jacobson, Lord, & Newman, 2017). Dukungan sosial penting untuk diberikan dalam mekanisme pemulihan ketika kematian pasangan (van Baarsen, 2002).…”
Section: Pendahuluanunclassified
“…Hasil ini sesuai dengan penelitian sebelumnya yang menunjukkan bahwa dukungan sosial sangat mempengaruhi situasi setelah kehilangan pasangan di masa tua. Dukungan sosial emosional dapat memediasi antara gejala kecemasan dan gejala depresi pada orang tua yang telah kehilangan pasangan (Davies et al, 2016;Jacobson et al, 2017). Dukungan sosial penting untuk diberikan dalam mekanisme pemulihan ketika kematian pasangan (van Baarsen, 2002).…”
Section: Pembahasanunclassified
“…These findings indicate the acceptability of the program contents and structure to these participants. Previous studies have indicated that older people with loneliness, anxiety and depression can find it difficult to enjoy activities and tend to socially withdraw (Cruwys et al, 2014;Jacobson et al, 2017). Conversely, these findings suggest that for this sample, the SRT program gave enjoyment and facilitated social interaction and emotional connection.…”
Section: Discussionmentioning
confidence: 54%
“…More recently, a study involving 250 older people in the United States of America found that anxiety positively predicted depression (B =0.331, CI =0.004−0.682, d=0.271), especially within 48 months of bereavement (Jacobson, Lord, & Newman, 2017). Altogether, these studies provide good evidence of an association between loneliness and depression, loneliness and anxiety, and anxiety and depression among older people.…”
Section: The Significant Relationship Between Loneliness Anxiety Andmentioning
confidence: 85%